2011
DOI: 10.1016/j.hkpj.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian physiotherapists’ perceptions of their profession’s prestige and implications

Abstract: This study investigated Nigerian physiotherapists' perceived prestige of their profession relative to 11 selected occupations and how their perception was influenced by selected sociodemographics. A total of 368 copies of a questionnaire adapted from a previous study were sent to registered physiotherapists working in Nigeria as of May 2007. Data were analysed using Chi-square, Kendall's W, and multidimensional scaling analysis. Two hundred sixty copies of the questionnaire were completed and returned (70.7% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
18
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 8 publications
11
18
3
1
Order By: Relevance
“…Such issues could explain why one third of those who participated in our study reported a desire for a career change. This figure resembles the conditions applied to developing countries [19] .…”
Section: Discussionmentioning
confidence: 75%
“…Such issues could explain why one third of those who participated in our study reported a desire for a career change. This figure resembles the conditions applied to developing countries [19] .…”
Section: Discussionmentioning
confidence: 75%
“…The social standing or prestige of an occupation is frequently of interest to its professional members 8 . A previous study in Nigeria reported that the professions of physiotherapy is perceived as having a moderate level of occupational prestige 9 …”
Section: Introductionmentioning
confidence: 99%
“…Globally, many comprehensive studies have been carried out on perceptions of the profession of physiotherapy, as well as its role in healthcare. These studies have elicited information from different groups such as high school students, 11 future physiotherapists, 8 other medical practitioners,8, 12 and practicing physiotherapists 9 . Several studies have evaluated the profession relative to other occupations 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle bireyin modern toplumdaki sosyal konumu, kendisine kalan mirastan çok, büyük ölçüde mesleği veya ailesinin mesleği tarafından belirlenir. Ayrıca, bir insanın karakterinin, zekâ ve eğitim seviyesinin, kabiliyetinin ve kişisel kabul edilebilirliğinin mesleki etiketten alındığına dair kanıtlar söz konusudur (6). Bu bağlamda tıp, politika ve hukukla ilgili meslekler dahil olmak üzere bazı meslekler toplum tarafından güç, prestij ve maddi ödül ile ilişkilendirilmektedir (4)…”
Section: Introductionunclassified